Assessment of biomarkers influencing treatment success on small intestinal lymphoma in dogs. (21st September 2020) - Yamazaki, Hiroki; Sasai, Hiroshi; Tanaka, Miyuu; Tanaka, Toshiyuki; Nishida, Hidetaka; Noguchi, Shunsuke; Kuwamura, Mitsuru; Akiyoshi, Hideo
Abstract: This study aimed to determine a reliable therapeutic biomarker for localized small intestinal lymphoma (SIL) in dogs based on clinical and histopathological features. We retrospectively investigated 84 dogs with localized SIL, including 36 dogs receiving surgery and 48 dogs receiving chemotherapy. The dogs receiving surgery were divided into two subgroups: 18 dogs (group 1) with overall survival (OS) <120 days (median OS) and 18 dogs (group 2) with OS ≥120 days. Correspondingly, the dogs receiving chemotherapy were divided into 24 dogs (group 3) with OS <98 days (median OS) and 24 dogs (group 4) with OS ≥98 days. Clinical, haematological, histopathological and immunohistochemical analyses were comparatively evaluated among the four subgroups. There was no significant difference in OS between the surgery and chemotherapy groups. In dogs receiving surgery, the rate of Ki67‐positive cells was significantly increased in group 1 compared to group 2 and showed no significant difference between groups 3 and 4. In dogs receiving chemotherapy, the rate of O6‐methylguanine‐DNA methyltransferase (MGMT) was significantly higher in group 3 than in group 4 and showed no significant difference between groups 1 and 2. Additionally, our data showed that OS in dogs with higher Ki67 expression might be significantly increased by chemotherapy than by surgery, that of those with higher MGMT expression might be significantly increased by surgery than by chemotherapy, and Ki67 and MGMT were independent of each other. Indices of Ki67 and MGMT are suggested therapeutic biomarkers to determine the optimal first‐line treatment for localized SIL in dogs.